2022
DOI: 10.1177/10732748221074734
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CCN1 in Esophageal Adenocarcinoma: What We Have Learned From the Lab

Abstract: Background: Esophageal cancer is one of the most common and deadliest cancers in the world, particularly esophageal adenocarcinoma. There has never been a special drug to treat it. Purpose: This article summarizes the work that we have done in our laboratory about the role of CCN1 in esophageal cancer and gives a new perspective of CCN1 biology. Research Design: This is a review article. Study Sample: The work was done using validated cell lines and fixed human tissue slides. Data Collection and Analysis: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Studies have also shown that Cyr61 may activate Wnt, Shh, NF-κB, and COX2 signaling pathways in tumor cells. 24 - 26 Our study found that the expression of Cyr61 is closely related to Shh, indicating that these two proteins may promote each other in the progression of GC. Multivariate Cox proportional hazards regression analysis showed that patient age, Shh, Gli1, Cyr61 expression, TNM stage, and tumor differentiation were independent prognostic factors for OS in patients with GC.…”
Section: Discussionmentioning
confidence: 61%
“…Studies have also shown that Cyr61 may activate Wnt, Shh, NF-κB, and COX2 signaling pathways in tumor cells. 24 - 26 Our study found that the expression of Cyr61 is closely related to Shh, indicating that these two proteins may promote each other in the progression of GC. Multivariate Cox proportional hazards regression analysis showed that patient age, Shh, Gli1, Cyr61 expression, TNM stage, and tumor differentiation were independent prognostic factors for OS in patients with GC.…”
Section: Discussionmentioning
confidence: 61%
“…The reduction of acid secretion is simply not enough to stop GERD completely. Increasing evidence suggests that acid reflux may contribute to esophageal erosion but does not lead to malignancy; it is the bile reflux that induces the development of Barrett's esophagus and adenocarcinoma [26][27][28][29][30][31].…”
Section: Suppressing Stomach Acidmentioning
confidence: 99%
“…Progress has been made for esophageal cancer (EAC) where the evidence suggests that CCN1 can override the inflammatory tumor progression factor TNFα to induce TRAIL and CCN1 leading to apoptosis (Chang et al 2022). Ackar et al (2021) found CCN1 as a circulating biomarker in plasma for the detection of lung cancer.…”
Section: Introductionmentioning
confidence: 99%